Use of molecular markers SSR and SCAR for identification of olive accessions (Bioscience Journal, 2020)
Morphological and agronomical describers are traditionally used in plant characterization. However, the usage of these describers have some limitations such as susceptibility to abiotic and biotic stress and environmental factors. Furthermore, the describers are not stable over time and many can only be evaluated during the adult phase of the plants, which requires time and physical space. Molecular markers offer numerous advantages compared to the conventional alternatives based on phenotype: they are stable and detectable in all vegetable tissues, and are independent of the environment and development phase. One of the main advantages of the use of molecular markers is the time reduction in the identification of genetic diversity among the studied subjects, as the genotypes may even be described for the seed or seedling phase. Many countries have already adopted molecular markers to identify olive cultivars more accurately. The aim of this study was to evaluate the genetic identity of eight olive accessions supposedly belonging to cultivar Arbequina by using microsatellite (SSR) and Sequence Characterized Amplified Region (SCAR) markers. One accession corresponding to the cultivar was also incorporated into the analysis as a reference genotype. The molecular marker data were analyzed on the software GENALEX6. The markers generated an accumulated PI and PE of 1.26 x 10-6 and 0.949, respectively. The results supported the hypothesis that all accessions belong to the cultivar Arbequina, and the markers can therefore be applied to other varieties of olive species.